PENGARUH CSR, PROFITABILITAS, LEVERAGE. LIKUIDITAS, DAN FIRM SIZE TERHADAP AGRESIVITAS PAJAK - Jonathan, Edbert; Ade Onny Siagian (Jurnal Bisnis Terapan, 2025)
This quantitative study aims to analyze the influence of CSR, Profitability, Leverage, Liquidity, and Firm Size on Tax Aggressiveness in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research context stems from the crucial role of tax as the state’s fiscal backbone, which is often challenged by corporate tax aggressiveness—a strategy to minimize tax burden that potentially impedes state revenue and economic growth. Secondary data were collected from company financial reports and analyzed using the multiple linear regression method with the aid of SPSS version 27. Tax Aggressiveness was measured using the Effective Tax Rate (ETR) proxy. The results indicate that, simultaneously, all independent variables (CSR, Profitability, Leverage, Liquidity, and Firm Size) significantly influence Tax Aggressiveness. However, partially, only Leverage was found to have a significant influence, while CSR, Profitability, Liquidity, and Firm Size did not have a significant influence. The study concludes that the level of Leverage is the single most important factor individually influencing corporate tax strategy in the energy sector, while the combination of all factors collectively has a significant impact on Tax Aggressiveness decisions.